Monte Carlo Simulations of scintillation detectors for the use as dosemeters. (15th September 2021) - Alegria, N.; Kessler, P.; Gabay, K.-L.; Legarda, F.; Neumaier, S.; Röttger, A.
Abstract: The energy dependent conversion factors from measured photon pulse height spectra to ambient dose equivalent (H * (10)) of three different detectors based on the scintillation materials CeBr_3, LaBr3 and SrI2 were simulated with the three Monte Carlo Codes, GEANT4, MCNP and PENELOPE, respectively. The performance of the detection systems, using the calculated conversion factors (fitted to response functions), is demonstrated for different scenarios ranging from laboratory conditions (i.e. a precisely defined radiation field in a calibration facility) to a free-field irradiation scenario produced by the natural radioactivity at a large lawn. With very simple geometric models of the detector systems, the response function of scintillation based dosemeters can be derived from the aforementioned Monte Carlo simulations with an accuracy of the measured doses in H * (10) of ±10% in an photon energy range from 100 keV to 3000 keV, as being typical for natural environmental gamma radiation.